Pembuatan Bahan Ajar Digital Mata Pelajaran Akuntansi Keuangan di SMK Negeri 1 Tanjungpinang - Santi Yopie; Juliana Juliana (Universitas Internasional Batam, 2021)
This study aims to provide digital teaching materials for financial accounting subjects. Due to the pandemic situation that getting worse, resulting in the issuance of a new policy for online learning so most schools are still in the process of switching their learning methods to online. The sample selection in this writing is SMK Negeri 1 Tanjungpinang, focusing on financial accounting subjects in grade XII even semester. The method used in this writing includes observation, interviews, and documentation. The digital learning modules are prepared in accordance with the basic competencies used at SMK Negeri 1 Tanjungpinang and also adjust to the needs of the educator. The results of this writing are digital teaching materials in the form of modules, practice questions, and summaries that presented in Microsoft PowerPoint. The online learning method requires new teaching materials in digital form in order to facilitate the online learning process so that the results of the writing are expected to help teachers and students who are undergoing this new learning method.